From kitchen to consumer : the entrepreneur's guide to commercial food production - Nelson-Stafford, Barbara, 1951- (Academic Press, 1991)
This book contains all the factual, technical, and resource information anyone would need to successfully market and establish a food manufacturing business. It covers such topics as choosing a food product, developing that product, legal and economic aspects of the food marketing business, successful marketing, advertising, packaging, and food safety. It is a must for the would-be entrepreneur!